Men and masculinities in modern Britain - Houlbrook, Matt; Jones, Katie; Mechen, Ben (Manchester University Press, 2024)
This book offers a striking and pointed reflection on what histories of masculinity in modern Britain have been and where they might go next. Addressing the constant contemporary talk of crisis around men's lives, Men and Masculinities argues powerfully that we need histories of masculinity which are present-centred and politically engaged. In so doing, it sets out a new agenda for the field. Ranging over the past 130 years, a series of engaging and original essays trace how men, like masculinity, were made. In exploring that process, contributors demonstrate the radically different ways in which men made sense of the world and their place in it. The book provides compelling evidence of how individual life stories can transform how we think about the time- and place-specific formation of men's experiences and ideas of masculinity. Through vivid case studies that include trans men's encounters with the welfare state, the experience of wounded Jamaican servicemen, and the social world of the public librarian, the volume interweaves histories of masculinity with wider histories of society, culture, economy, and politics. It is on that basis that the work shows how thinking critically about histories of masculinity also provides new ways of understanding the making and remaking of modern Britain. Men and Masculinities both provides a critical genealogy for contemporary gender politics and the persistence of patriarchy and male power and establishes new ways of understanding how men's lives and ideas of masculinity have (and have not) changed in modern Britain.